Detection and characterization of vibrio parahaemolyticus in raw mackerel fish and fish-based street food - Syamimi Hanim, M.; Tan, J.Y.; Ho, L.H.; Kamarul'Ain, M. (2018)
This study aimed to investigate the prevalence of Vibrio parahaemolyticus in raw mackerel fish as well as fish-based products namely satar and otak-otak. A total of 120 fish, 90 satar and 35 otak-otak that have been purchased randomly in Terengganu were subjected to PCR and conventional. plating method for detection and isolation of V parahaemo!J1ticus. The isolates were characterized by 12 types of antibiotic using discs diffusion method. About 67.5%, 23.3% and 5.71% of fish, satar and otak-otak were contaminated with V parahaemolyticus. A total of 58 V parahaemolyticus isolates were recovered from fish. Among them, 24 of V parahaemolyticus isolates carried tdh gene and 3 isolates had trh gene. All the isolates were susceptible to amikacin, norfloxacin, ceftazidime, ciprofloxacin, and enrofloxacin. There was high resistant towards penicillin (93.1%), vancomycin (89.7%) and ampicillin (55.2%). About 56.9% of strains isolated showed a MAR index higher than 0.2, indicating these strains were from high risk sources of contamination. This study found V parahae111o!Jticus contaminated raw fish mackerel, satar and otak-otak.